Stand-level habitat characteristics and edge habitats drive biological pest control services in the understory of oil palm plantations - Denan, Nuradilah; Norhisham, Ahmad R.; Sanusi, Ruzana; Stone, Jake; Azhar, Badrul (Elsevier, 2023)
The expansion of oil palm agriculture in the tropics has gone hand in hand with a sharp increase in synthetic pesticide application in the region. Due to associated negative ecological impacts, there is growing pressure on the oil palm industry to reduce chemical usage and revert to natural pest control methods. However, knowledge of the mechanisms that govern how successful natural predators are at controlling pest insect species in the understory of oil palm plantations is scarce. By using an artificial caterpillar bait method this study examines the effectiveness of three animal taxa (i.e., arthropods, birds, and mammals) as within-plantation insect predators. Caterpillars were deployed across three different aged oil palm plantation plots in Selangor, Malaysia. Data for height and coverage of understory vegetation, plot location, elevation, and canopy cover were collected. Of the three taxa studied, mammals were responsible for the highest levels of predation, followed by arthropods and then birds. Arthropod predation was higher at edge locations, in abandoned habitats and in elevated areas. Mammal predation was shown to increase with increasing understory coverage and decrease with increasing elevation. Bird predation was not shown to be associated with any of the habitat quality characteristics studied. We found that overall predation pressure was higher at the edge of plantations compared to within plantation interiors, and that overall predation positively correlated with an increase in understory vegetation coverage. Management strategies that enhance undergrowth coverage and maximise edge habitats have the potential to boost the effectiveness of natural predators in the understory of oil palm plantations.